Veel vertier, weinig politiek - Dirk Jan Wolffram (BMGN: Low Countries Historical Review, 2014)
In his rich book Plaatsen van beschaafd vertier (Places of civilised pleasure) Jan Hein Furnée displays in a creative and exemplary manner the culture of the elite in The Hague in the nineteenth century. With his book he set a new standard for local cultural-historical research. However the book offers little additional value as a comparative approach is missing. Moreover, by choosing elite and bourgeois sociability as a point of departure, the book offers no new insights into the changes in nineteenth-century political culture.